The Translatability of Arabic Jokes into English - El-Yasin, Mohammad (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThis paper deals with the translatability of linguistic jokes from Arabic into English. These jokes are primarily based on incongruities in the language. The paper discusses a sample of jokes utilizing puns, homonyms, idioms, rhymes and collocations. There is sufficient evidence that translating Arabic jokes into English is not possible. Such a translation poses cultural and, more seriously, linguistic problems for the translator owing to the two incompatible meanings of a linguistic form in a given joke which are accidental facts about Arabic and do not have equivalents in the target language. Consequently, it is concluded that linguistic jokes in Arabic cannot be easily and straightforwardly rendered in English.